Vaginal Microbiome Signature Is Associated With Spontaneous Preterm Delivery - Hočevar, Keli; Maver, Aleš; Vidmar Šimic, Marijana; Hodžić, Alenka; Haslberger, Alexander; Premru Seršen, Tanja; Peterlin, Borut (Frontiers in Medicine, 2019)
Background: Preterm delivery (PTD) represents an important public health and therapeutic challenge. Despite the reported link between the composition of vaginal microbiome and PTD, previous studies were inconsistent in their conclusions and utilized non-uniform designs. We performed an independent case-control study carried out on the Slovenian population, where we re-evaluated the role of the vaginal microbiome in PTD. Methods: Vaginal microbiomes of pregnant women who delivered preterm were compared to those delivered at term to examine differences in the microbial richness, diversity, and differential abundance of specific taxa. We obtained vaginal swab samples from 155 Caucasian women who were classified as either term (≥380/7 weeks, n=107) or preterm (≤366/7 weeks, n=48) in exclusion of any other medical or obstetric conditions. The vaginal microbiomes of these women were characterized by 16S ribosomal RNA (rRNA) gene sequencing of the V3-V4 region on the MiSeq platform. Results: Women who experienced PTD had a higher microbial richness (Chao1, P=0.011) and alpha diversity (Shannon, P=0.00059) than women with term deliveries. We report that overall vaginal microbial community composition (beta-diversity) was significantly different by delivery gestational age category (PWeighted Unifrac<0.001). Women who delivered preterm had decreased Lactobacilli spp. abundance as well as increased abundance of Gardnerella and other bacterial vaginosis (BV) and aerobic vaginitis (AV) associated genera including Atopobium, Sneathia, Gemella, Megasphaera, Dorea, Streptococcus, and Escherichia/Shigella. Conclusions: In the present study, we provide further evidence that vaginal microbiome composition is associated with PTD.